Elaboração e estudo de comportamento de formulações de "BEBIDAS LÁCTEAS" com fibras potencialmente prebióticas - Pereira, Renato Alves (2023)
Functional foods are gaining more and more space in the food industry. New technologies have helped to obtain products with better characteristics and cost. Recently, industries and the Ministry of Health committed to reducing the percentage of sugar in several processed foods, including dairy drinks, with a target for a reduction of up to 62% of this ingredient for 2022. Based on this goal and with a focus on creating alternatives to reduce the impact on sugar reduction and become viable alternatives, this project developed, with the help of experimental planning, formulations of fermented milk drinks, varying the percentages added of sugar, milk protein and potentially prebiotic fibers. The prebiotic fibers that were part of the formulations were Xylo oligosaccharide (XOS) and Isomalto oligosaccharide (IMO) fiber. These formulations were developed using Central Composite Rotational Design (DCCR), with the ingredients defined as variables, milk protein, sugar and fiber. The formulations were prepared, stored under refrigeration for 45 days and evaluated for pH, serum separation (syneresis) and rheological behavior. The results were statistically analyzed based on the interactions of the three variables, as well as their effects over time. The results were presented in order to highlight how the percentage of each variable influenced the evaluated parameters (pH, syneresis and viscosity). Throughout the analysis period, it was possible to conclude that the protein variable played a prominent role in both formulations with prebiotic fiber, but it also indicated that, comparing the formulations with both fibers, the formulations with IMO showed lower pH variation, lower serum separation(Syneresis), where the formulations with the highest index, which was recorded after 45 days of storage, were 16.66mL for XOS(F13) and 13.67mL for IMO(F13), for viscosity values, the IMO formulations presented higher values, reaching 1118.35cP (F14/30days) while for XOS, the highest value was 596.78cP (F7/07days), all at shear stress of 50 s-1. Another finding was that both can be incorporated into formulations, without harmful impacts, which leads to the conclusion that fibers tend to be an interesting option, taking into account only the parameters studied.